Protein expression in the liver and blood serum in chickens in response to Salmonella Enteritidis infection - Polansky, Ondrej; Seidlerova, Zuzana; Faldynova, Marcela; Sisak, Frantisek; Rychlik, Ivan (Veterinary immunology and immunopathology, 2018)
Events occurring in the chicken caecum following Salmonella Enteritidis infection are relatively well-described. However, mechanisms of the immune response and defence beyond the intestinal tract are less well-described. In this study, we therefore determined changes in protein abundance in the liver and blood serum in response to S. Enteritidis infection using the unbiased approach of shotgun proteomics. Complement and coagulation cascades, TNF signalling, antigen processing and presentation was activated in the liver following infection with S. Enteritidis. Chicken proteins that decreased in the liver were involved in glycolysis, the citrate cycle, oxidative phosphorylation and fatty acid metabolism. No functional category was significantly activated or suppressed in the serum. Concerning individual proteins, VNN1, SAA, AVD, SERPINA3, SERPINB10, AGT, MRP126 or CP increased in abundance both in the liver and serum. MT4, MT3, PTGDS, GLRX and TGM4, though highly inducible in the liver, did not increase in the serum. PIGR, SERPINF2 and IGJ increased in the serum but not in the liver. SERPINA4, apoAIV, CLEC3B, SERPINF1, HRG, AHSG and ALB decreased both in the liver and serum. Avidin-like LOC431660, THRSP, GATM, GGACT, ACOX1, ALDOB or FABP7 decreased in the liver but not in the serum. Finally, CKM, CKB, PLTP, COMP, IGFALS, AMY1A or SERPIND1 decreased in the serum after S. Enteritidis infection but not in the liver. Differently abundant proteins characterise the chicken's response to infection and can be also used as markers of chicken health status.
Keywords: Liver; prezentace antigenu; játra; Acute-Phase Proteins; proteomika; cékum; Antigen Presentation; Salmonella enteritidis; nemoci drůbeže; Salmonella; Serum; kur domácí; Acute phase protein; Proteomics; Chickens; Chicken; zvířata; proteiny akutní fáze; Poultry Diseases; Cecum; salmonelová infekce u zvířat; Salmonella Infections, Animal; Animals